IMPROVING THE PRACTICE OF EVALUATING THE INVESTMENT POTENTIAL OF SMALL BUSINESSES - Ergashev Ilkhomjon Ikromovich, Ergashev Ilkhomjon Ikromovich (THE INNOVATION ECONOMY, 2025)
: in the article, the national method for assessing the effectiveness of investments is reflected in analytical approaches that are specific to the country's economy and reflect the general characteristics for various industries and sectors of the economy of the Republic. Proposals and recommendations have been developed for dividing the factors affecting the efficiency of investment activities of enterprises into different groups according to the degree of interconnection.